2009
DOI: 10.1152/ajpgi.00087.2009
|View full text |Cite
|
Sign up to set email alerts
|

Vascular cell adhesion molecule-1 expression in human intestinal microvascular endothelial cells is regulated by PI 3-kinase/Akt/MAPK/NF-κB: inhibitory role of curcumin

Abstract: Endothelial activation and surface expression of cell adhesion molecules (CAMs) is critical for binding and recruitment of circulating leukocytes in tissues during the inflammatory response. Endothelial CAM expression plays a critical role in the intestinal microvasculature in inflammatory bowel disease (IBD), as blockade of leukocyte alpha4-integrin binding by gut endothelial CAM ligands has therapeutic benefit in IBD. Mechanisms underlying expression of vascular cell adhesion molecule (VCAM)-1, a ligand for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 35 publications
6
44
0
Order By: Relevance
“…Consistent with previous reports demonstrating that the tyrosine phosphorylation of p38 MAPK and ERK is involved in signal transduction occurring in LPS-stimulated endothelial cells (23,38), and further mediates cellular Figure 8. Lipopolysaccharide (LPS)-induced nuclear factor-κB (NF-κB) translocation is suppressed by chitosan oligosaccharides (COS) in a dose-dependent manner in porcine iliac artery endothelial cells (PIECs).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous reports demonstrating that the tyrosine phosphorylation of p38 MAPK and ERK is involved in signal transduction occurring in LPS-stimulated endothelial cells (23,38), and further mediates cellular Figure 8. Lipopolysaccharide (LPS)-induced nuclear factor-κB (NF-κB) translocation is suppressed by chitosan oligosaccharides (COS) in a dose-dependent manner in porcine iliac artery endothelial cells (PIECs).…”
Section: Discussionsupporting
confidence: 91%
“…Binion et al [28] reported that the activation of Akt further caused activation of MAPK pathways. Stimulating chondrocytes by IL-1β has been shown to induce phosphorylation and activation of ERK1/2, JNK, and p38 MAPKs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, studies have been conducted to investigate the correlation between the AKT activity and its expression of cell adhesion molecules. Some of these studies have focused on the regulation of PI3-kinase/Akt/MAPK/NF-kappaB in the expression of vascular cell adhesion molecule-1 (VCAM-1) in human intestinal microvascular endothelial cells [21]; these studies have also observed withaferin A inhibition on VCAM-1 expression by blocking Akt and downregulating NF-kappaB activity [22]. In contrast to conventional cell adhesion molecules, hepaCAM largely functions as a tumor suppressor gene, but the correlation between AKT activity and hepaCAM expression of the primary tumor has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%